Public Health Behavior Change Communication Strategies in Accelerating the Reduction of Stunting in North Minahasa Regency - Reiner Richard Onsu; Grace Jane Waleleng; Joula J. Rogahang (Borong Newinera Publisher, 2023)
Communication Strategy for Community Health Behavior Change in Accelerating Stunting Reduction in North Minahasa Regency, through aspects (1) Announcing: socialization and counseling to pregnant women and parents who have children under 5 years old through lectures, presentations and questions and answers. (2) Motivating: Pay attention to nutritional intake, Conduct regular health checks for pregnant women and toddlers, Overcome the problem of children having difficulty eating by providing variants in food, Maintain environmental sanitation, provide education to pregnant and lactating women in the